Plan de negocio para la elaboración de bebidas a base de café en la ciudad de santa marta: Elegant Coffe (2024)
The following business plan for the production of coffee-based drinks in the city of Santa Marta, Elegant Coffe, as its name indicates, is based on the creation of coffee-based drinks in the city of Santa Marta, it is It will stand out for its innovative and delicious drinks. One of the most emblematic products of Colombian culture was taken as a source of inspiration, however, this ambitious initiative was born from two young people who decided to face considerable challenges such as the positioning of the “Elegant Coffee” brand. Elegant Coffee has the potential to contribute to the small farmers who are located in the Sierra Nevada de Santa Marta, given that the product used to make these delicious drinks is distributed by these small farmers, and it also gives them participation. for the creation of small and medium-sized businesses in order to satisfy the needs of consumers with the variety of unmatched flavors.